How Do Age-Related Policy Reforms Promote Employment among Older Adults in Singapore? - Jessica Ya Sun; Emiko Usui (Institute of Labor Economics (IZA), 2022)
This study uses data from the Singapore Life Panel to investigate the effects of age-related policy reforms on older adult labor supply behaviors in Singapore. We first evaluate the impact of the Retirement and Re-employment Act (RRA) reform in 2017, which raised the maximum re-employment age from 65 to 67 years for those who were able to claim pension benefits at age 64. We find that the RRA reform reduced the probability of unemployment among people aged 66 years by 5.8 percentage points and increased the probability to continue working in the longest-held job during the lifetime by 11.4 percentage points. Second, we examine the impact of the pension-eligibility age reform of 2018, which raised the pension-eligibility age from 64 to 65 years for those who were protected by the mandatory labor protection and re-employment policy up to the age of 67 years. This rise in the pension-eligibility age increased the probability of full-time employment by 8.2 percentage points and reduced the probability of part-time employment by 5.7 percentage points among people aged 64 years. These two reforms promoted employment among older adults in different ways. Specifically, enhanced employment protection at age 66 increased the older adults' labor supply in the extensive margin, resulting in a welfare improvement for older adults since those who had been underemployed were less likely to be so after the reform. Still, their ineligibility to claim their pension at age 64 lowered their economic well-being because it increased their labor supply in the intensive margin to supplement the delay in pension benefits.
Keywords: H55; J22; J26; 330; pension reform; retirement; older adult; Singapore